PROPAGANDA DALAM EDITORIAL MEDIA INDONESIA - Winda Primasari (Fakultas Komunikasi, Sastra, dan Bahasa, 2012)
Though it was introduced more than fifty years ago at the era of cold war, the term propaganda is still relevant to be discussed and studied further. The purpose of propaganda is still the same – to make the audience or mass receive all kinds of information produced by propagandist without any doubts and hestitations. The practice of propaganda nowadays is not restricted in the war domain but also in any social domains. This study tries to find out how the media use editorial page as a mean of propaganda and what kind of propaganda strategies used. With social semantic approach, it is revealed that the propaganda in media are conduceted in three ways; by creating a field of discourse that oppose the goverment and label it negatively; by involving high-rank tenor of discourse such as the Ministers and Secretary Generals; by applying hiperbolic, rhetoric and ironic mode of discourse to support the field and tenor of discourse. The propaganda strategies used are mostly name calling, glittering generality, bandwagon, and testimonial.